2006
DOI: 10.1097/01.brs.0000219873.84232.26
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for Improvement in Different Back Pain Measures and Their Influence on the Duration of Sickness Absence

Abstract: Except for male gender, the primary determinants for improvement in pain, functional limitations, and quality of life were not associated with RTW. Although there is a large coherence in the improvement in the outcome measures, RTW seems primarily determined by the level of experienced functional limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The study population of workers on sick leave for 2-6 weeks had pain intensity, functional limitations and general health comparable with that of workers on sick leave due to back pain between 7 and 12 weeks (10,(27)(28). Within this population 45% of the workers experienced a recurrence of musculoskeletal sick leave within the follow-up period, which was on average approximately 9 months.…”
Section: Resultsmentioning
confidence: 88%
“…The study population of workers on sick leave for 2-6 weeks had pain intensity, functional limitations and general health comparable with that of workers on sick leave due to back pain between 7 and 12 weeks (10,(27)(28). Within this population 45% of the workers experienced a recurrence of musculoskeletal sick leave within the follow-up period, which was on average approximately 9 months.…”
Section: Resultsmentioning
confidence: 88%
“…One large US national study of employed people showed the overall productive time lost due to pain did not differ by gender, but women were more likely to lose work time due to headache and men due to back pain [44]. On the other hand, studies of long-term disability outcomes consistently indicate women with disabling musculoskeletal injuries recover less quickly [9,33,43] and return to work later than men [10]. However, women may be more likely to stay at work once they return [6].…”
Section: Discussionmentioning
confidence: 95%
“…This may be explained by learned management as patients with previous LBP episodes would have a better idea of their condition progression and how to cope with their symptoms. [ 25 ] This experience may consequently influence their perception of pain intensity.…”
Section: Discussionmentioning
confidence: 99%